Flint Type Analysis at Late Acheulian Jaljulia (Israel), and Implications for the Origins of Prepared Core Technologies - Agam, Aviad; Rosenberg-Yefet, Tamar; Wilson, Lucy; Shemer, Maayan; Barkai, Ran (Frontiers in Earth Science, 2022)
Prepared Core Technologies, often considered a hallmark of the Middle Paleolithic Mousterian, have recently been observed, to some extent, in many late Lower Paleolithic Acheulian sites. This may indicate a Lower Paleolithic origin of the Levallois method, although the circumstances leading to its emergence, spread and assimilation are still debated. We aim at contributing towards this intriguing issue by studying patterns of flint procurement and exploitation at Late Acheulian Jaljulia (Israel; ~500-300kya). We classified artifacts into flint types, using four samples: a general sample, bifaces, 'regular' cores with one/two striking platforms, and prepared cores, divided into proto-Levallois, prepared (general) and discoid cores. A geologic survey located potential flint sources, and a petrographic analysis was used to assign flint types to sources. Our results show that while local Turonian flint of the Bi'na Formation dominates the general sample, selectivity in using specific flint types was observed, including among local materials. While brecciated flint types are especially common among handaxes and discoid cores, among proto-Levallois and prepared cores (general), fine-textured homogenous flint types are more common, suggesting that such flint types are better-suited when improved control over the end-product was desired. Based on our results, and following previous suggestions, we support the hypothesis that prepared core technologies in the Levant did not originate from one single technological trajectory. We support the idea that the production of predetermined blanks was based on knowledge gathered from several technological trajectories, including mainly biface shaping and the production of flakes from regular cores. This novel method was most likely transmitted time and again between individuals, gradually adjusting it to produce improved end-products. We see these conclusions as additional support for the view of prepared core technologies at the Late Acheulian as a demonstration of cumulative culture, and the existence of high-fidelity social learning mechanisms in practice already during the late Lower Paleolithic of the Levant.